Validation of clinical‐grade whole genome sequencing reproduces cytogenetic analysis and identifies mutational landscape in newly‐diagnosed multiple myeloma patients: A pilot study from the 100, 000 Genomes Project. Issue 4 (26th August 2021) - Lomas, Oliver C.; Gooding, Sarah; Cabes, Maite; Dreau, Helene; Wilson, Edward; Polzella, Paolo; ,; Ramasamy, Karthik; Hamblin, Angela D.
Abstract: Multiple myeloma is characterized by chromosomal abnormalities and genetic variation, which may inform prognosis and guide treatment. This pilot study sought to examine the feasibility of incorporating Whole Genome Sequencing (WGS) alongside the routine laboratory evaluation of 14 patients with newly diagnosed multiple myeloma who had enrolled in the 100, 000 Genomes Project. In all 14 cases, WGS data could be obtained in a timely fashion within existing clinical frameworks in a tertiary hospital setting. The data not only replicated standard‐of‐care FISH analysis of chromosomal abnormalities but also provided further chromosomal and molecular genetic insights that may influence patient management.